1997
DOI: 10.1115/1.2801220
|View full text |Cite
|
Sign up to set email alerts
|

Robust Nondiagonal Controller Design for Uncertain Multivariable Regulating Systems

Abstract: Presented in this paper is a robust controller design methodology for a class of uncertain, multivariable, regulating systems required to maintain a prespecified operating condition within hard time domain tolerances despite a vector of step disturbances. The design methodology is a frequency domain approach and is based on sequential loop design where a Gauss elimination technique facilitates the various design steps. The specific class of systems addressed are those which can be modeled as square, multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…Different solutions were proposed in the literature to deal with different variations of this problem [2], [3], [4], [5], [6], [7]. The approach applied in this paper [8] integrates previous techniques [6], [9], [10] and designs a fully populated controller for multivariable systems.…”
Section: Qwurgxfwlrqmentioning
confidence: 99%
See 2 more Smart Citations
“…Different solutions were proposed in the literature to deal with different variations of this problem [2], [3], [4], [5], [6], [7]. The approach applied in this paper [8] integrates previous techniques [6], [9], [10] and designs a fully populated controller for multivariable systems.…”
Section: Qwurgxfwlrqmentioning
confidence: 99%
“…This is only a sufficient condition to guarantee the stability of the system. Consequently, the designer must pay close attention to systems with non minimum phase or unstable elements [7], [16].…”
Section: )7 7khru\mentioning
confidence: 99%
See 1 more Smart Citation
“…These terms could then be used to reduce the level of coupling in open loop, and therefore reduce the amount of feedback needed in the diagonal compensators to fulfil the required specifications (Horowitz, 1982). Furthermore, as (Franchek et al, 1997) demonstrated, non-diagonal compensators can be used for ensuring that no SISO loop introduces extra unstable poles into the subsequent loops in sequential procedures based on the inverse plant domain, e.g. Horowitz's second method (Horowitz, 1982), -accordingly, this is not possible in Mayne's (Mayne, 1973;, or Park's (Park et al, 1994) framework-.…”
Section: Overviewmentioning
confidence: 99%
“…The full-matrix pre-compensator is accordingly designed to reduce the coupling before designing a diagonal QFT controller. On the other hand, Franchek and collaborators (Franchek et al, 1995), (Franchek et al, 1997) introduced a non-diagonal sequential procedure. They made use of the Gauss elimination technique (Bryant , 1985) to introduce the effects of the controllers previously designed by means of a recursive expression.…”
mentioning
confidence: 99%